Seni pada Masa Pemerintahan Dinasti Abbasiyah Tahun 711 – 950 Masehi - Shubhi Mahmashony Harimurti (Jurnal Kajian Seni, 2016)
After the death of Prophet Muhammad SAW, Islam has got the glory. The gold eradidn’t see based on the territory. But it has been seen according to the particularly sector.Such as: arts, the building architecture, culture, and education. All of the successes havebeen got at Abbasid Dynasty. This dynasty is different with the other kingdom, suchas Umayyad that more concentrated in expansion mission. If discuss about Abbasid,public will know about Abu Nawas, Caliphate Harun al-Rashid, Baghdad, or 1001nights stories. Abbasid Dynasty is more inclusive than Umayyad Dynasty. This kingdompermitted to all of arts especially music. This decision is different with Umayyad onethat often prohibited the music in every society activities. In this simple paper, discussabout arts improvement at Abbasid Dynasty that one of the Baghdad glory indicator.